RE-ASSESSMENT OF MITIGATION STRATEGIES FOR DELIBERATE RELEASES OF ANTHRAX EMPLOYING A REAL-TIME OUTBREAK CHARACTERIZATION TOOL - PARIC, DR.G.PARIC; ZORIC, PRO.DS. ZORIC (International Journal of Multidisciplinary Research and Studies, 2021)
Responding rapidly and appropriately to a covert anthrax release is a crucial public health challenge. a strategy to help the geographical targeting of such a response has recently been published; as have several independent studies that investigate mitigation strategies. Here, we review and mix a number of these published techniques to more realistically assess how key aspects of the general public health response might impact the outcomes of a bioterrorist attack. We combine a within-host mathematical model with our spatial back-calculation method to research the consequences of several important response variables. These include how previously reported levels of adherence with taking antibiotics might affect the full outbreak size compared to assuming full adherence. Post-exposure vaccination is additionally considered, both with and without the employment of antibiotics. Further, we investigate a variety of delays (2, 4, and eight days) before interventions are implemented, following the Last Day of symptomatic onset of some number of observed initial cases (5, 10, and 15). Our analysis confirms that outbreak size is minimized by implementing prophylactic treatment after having estimated the exposed area supported 5 observed cases; however, imperfect (rather than full) adherence with antibiotics leads to approximately 15% additional cases. Moreover, of these infected individuals who only partially adhere to a prophylactic course of antibiotics, 86% remain disease-free; a result that holds for scenarios within which infected individuals inhale much higher doses than considered here. Increasing logistical delays have a very detrimental effect on lives saved with an optimal strategy of early identification and analysis. Our analysis shows that it’s critical to own systems and processes in situ to rapidly identify, geospatially analyze then swiftly reply to a deliberate anthrax release.